Food taboos among pregnant and lactating mothers in Tumkur: a qualitative study - T. M., Shwetha; R., Swetha; Iyengar, Krishna; S., Usha Rani (International Journal Of Community Medicine And Public Health, 2017)
Background: Maternal nutrition has a huge impact on the health of the mother and the fetus. Pregnancy imposes the need for considerable extra calorie and nutrient requirements. A food taboo is a prohibition against consuming certain foods. The restrictions imposed on people forces them to abstain from certain food and drinking items as these things are embedded into the cultural and religious threads. Methods: A qualitative study was conducted between July 2014 and September 2014. Study was conducted in urban and rural field practice area of Sri Siddhartha medical college, Tumkur, Karnataka. Study involved three groups Mother –in- laws Anganwadi workers, Pregnant and lactating women. Six Focus group discussions were conducted and four themes were used. Quantitative data was tabulated and analyzed using SPSS version 16. Results: All most all women under the study followed some form of restrictive diet. Many nutritive and locally available foods were avoided which includes fruits, vegetables, pulses and green leafy vegetables. Special foods rich in energy were consumed during post-partum period. Concept of hot and cold food is prevailing high and there was no scientific reasoning given for the taboo. Anganwadi workers who are front line health workers were believed in the many of the food taboos. Conclusions: Food taboos in this community are deep rooted. Avoidance of nutritive food was common in both the religion. Many misconceptions are prevalent which do not have scientific basis. Maternal nutrition needs to be prioritized at community level among family members and front line workers. Anganwadi workers need to be sensitized regarding different beliefs about food consumption during pregnancy and lactation.